CONCEPTUAL MODELS OF FUNCTIONAL ARCHITECTURE OF MOBILE RECONFIGURABLE AGENT-ORIENTED DISTRIBUTED COMPUTING SYSTEMS - Volchikhin, V. I.; Zinkin, S. A.; Karamysheva, N. S. (Известия высших учебных заведений. Поволжский регион:Технические науки, 2020)
Background. At the current level of organization of distributed computing systems (DCS), it is necessary to take into account the mobility of components - computing nodes located on mobile platforms and software modules in the form of mobile agents. The organizing of the interactions of components in virtualized cloudnetwork DCS (CN DCS), the software of which is based on the platforms of mobile and stationary agents, and the hardware includes stationary and mobile computing nodes, is an urgent and complex problem. The object of the research is the functional architecture of the CN DCS. The subject of the research is a methodology for constructing a conceptual model of distributed computing in CN DCS. The aim of the study is to create a simple conceptual model (CM) of CN DCS, combining the properties of cloud and grid systems with the properties of multi-agent systems and suitable for the subsequent creation of software for applied and middleware levels of CN DCS by sequential detailing of the CM. Materials and methods. During the research process, a model of a network of multi-tape Turing machines has being built and formalized specifications of network nodes are developed based on the theory of networks of abstract modules and executable logical-algebraic models. Results. A generalized conceptual model of the functional architecture of an agent-oriented cloud-network DCS with variable structure and mobile software based on a network of multi-tape Turing machines is proposed. The new unified descriptions of the elements of the conceptual model - deterministic, non-deterministic and probabilistic Turing machines with variable configuration based on the apparatus of formalized specifications - networks of abstract modules are proposed. Conclusions. A method for constructing a generalized conceptual model of the functional architecture of an agent-based CN DCS with a variable structure and mobile software based on a network of Turing machines, which allows a developer to evaluate the properties and determine the composition of DCS software of this type is proposed. It is assumed that, in practice, such a model is also suitable for the implementation on its basis of prototype software for systems of distributed and parallel symbolic multiprocessing of data.